2015
DOI: 10.1038/mt.2015.87
|View full text |Cite
|
Sign up to set email alerts
|

Coformulation of a Novel Human α -Galactosidase A With the Pharmacological Chaperone AT1001 Leads to Improved Substrate Reduction in Fabry Mice

Abstract: Fabry disease is an X-linked lysosomal storage disorder caused by mutations in the gene that encodes α-galactosidase A and is characterized by pathological accumulation of globotriaosylceramide and globotriaosylsphingosine. Earlier, the authors demonstrated that oral coadministration of the pharmacological chaperone AT1001 (migalastat HCl; 1-deoxygalactonojirimycin HCl) prior to intravenous administration of enzyme replacement therapy improved the pharmacological properties of the enzyme. In this study, the au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…The 1-deoxygalactonojirimycin (DGJ), a pharmacological chaperone, served as a positive control to evaluate the sensitivity of our established GLA-null cells as the platform for screening of the potential drug candidates in maintenance of the intracellular rhα-GLA stability. Previous studies have indicated that 10–100 µM DGJ is sufficient for sustaining the rhα-GLA activity [18,20] As shown in Figure 3C,E, cells co-treated with DGJ significantly increased the rhα-GLA protein levels and the GLA enzyme activity, respectively, in a dose-dependent manner. Collectively, these results suggested that the GLA-null cells are feasible and capable of screening potential drug candidates for maintaining intracellular rhα-GLA stability.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The 1-deoxygalactonojirimycin (DGJ), a pharmacological chaperone, served as a positive control to evaluate the sensitivity of our established GLA-null cells as the platform for screening of the potential drug candidates in maintenance of the intracellular rhα-GLA stability. Previous studies have indicated that 10–100 µM DGJ is sufficient for sustaining the rhα-GLA activity [18,20] As shown in Figure 3C,E, cells co-treated with DGJ significantly increased the rhα-GLA protein levels and the GLA enzyme activity, respectively, in a dose-dependent manner. Collectively, these results suggested that the GLA-null cells are feasible and capable of screening potential drug candidates for maintaining intracellular rhα-GLA stability.…”
Section: Resultsmentioning
confidence: 61%
“…Administration of the selective PCs to the mutated α-Gal A, particularly the missense mutants [11,12], facilitates the mutated α-Gal A to pass the protein quality control system in endoplasmic reticulum (ER) and potentiates their folding, maturation and/or cellular trafficking, hence resulting in effective lysosomal delivery of α-Gal A [13,14,15,16]. In addition, the selective PC was reported to enhance the ERT efficacy in vivo by prolonging rhα-GLA stability and reducing rhα-GLA degradation [17,18]. These results suggested that the proteostasis network, which consists of pathways that influence protein synthesis, folding, trafficking, disaggregation and degradation in cells, plays an important role in ERT efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…DGJ can be used in synergy with ERT either co-administrating both drugs intravenously or one orally (DGJ) and the other intravenously (recombinant enzyme). DGJ prolongs the half-life of AGAL in vivo, both in mouse models and in humans and leads to an improved clearance of Gb3 [44,45,46]. …”
Section: Introductionmentioning
confidence: 99%
“…Development of antibodies against the infused enzyme has been observed in some patients [13][14][15]. Other treatments such as chaperone therapy [16,17] and substrate reduction therapy [18] are also under investigation.…”
mentioning
confidence: 99%